Implementasi Pengamanan Swakarsa Berbasis Partisipasi Masyarakat dan Teknologi di Kompleks Perumahan - Lidya Novega; Rahman Amin (Jurnal Kajian Ilmu Kepolisian dan Anti Korupsi, 2025)
Security is one of the important factors in human life because with a sense of security, everyone can carry out their daily activities without fear of threats to their souls, bodies and property. However, in reality, the community has not fully realized that security is the responsibility of all components of society and is not only the duty and responsibility of the police as a state tool in the field of security, so the active participation of the community in self-defense is very necessary. This research is normative-empirical legal research with a legislative approach, a case approach and a conceptual approach to answer the problems raised. The results of the research are, First, the provisions on self-defense according to positive law in Indonesia are regulated in Law Number 2 of 2002 concerning the National Police, and further provisions are regulated in Police Regulation Number 4 of 2020 concerning Self-Defense which is the legal basis for the duties and roles of forms of self-defense in Indonesia, including the Security Unit and the Environmental Security Unit. Second, the implementation of self-defense based on community participation and technology in the Taman Duren Sawit Housing Complex, East Jakarta, which is the location of this research, has been carried out by the Security Unit Officers and involves the participation of community members in mobile patrol activities as well as the use of technology devices such as CCTV cameras and WhatsApp and Telegram digital applications for communication, information sharing and reporting on security situations in their neighborhoods each so that it can facilitate and increase the efficiency of the security system